Implementation and validation of a new operational wave forecasting system of the Mediterranean Monitoring and Forecasting Centre in the framework of the Copernicus Marine Environment Monitoring Service - Ravdas, Michalis; Zacharioudaki, Anna; Korres, Gerasimos (Natural Hazards and Earth System Sciences, 2018)
Within the framework of the Copernicus Marine Environment Monitoring Service (CMEMS), an operational wave forecasting system for the Mediterranean Sea has been implemented by the Hellenic Centre for Marine Research (HCMR) and evaluated through a series of preoperational tests and subsequently for 1 full year of simulations (2014). The system is based on the WAM model and it has been developed as a nested sequence of two computational grids to ensure that occasional remote swell propagating from the North Atlantic correctly enters the Mediterranean Sea through the Strait of Gibraltar. The Mediterranean model has a grid spacing of 1∕24∘. It is driven with 6-hourly analysis and 5-day forecast 10 m ECMWF winds. It accounts for shoaling and refraction due to bathymetry and surface currents, which are provided in offline mode by CMEMS. Extensive statistics on the system performance have been calculated by comparing model results with in situ and satellite observations. Overall, the significant wave height is accurately simulated by the model while less accurate but reasonably good results are obtained for the mean wave period. In both cases, the model performs optimally at offshore wave buoy locations and well-exposed Mediterranean subregions. Within enclosed basins and near the coast, unresolved topography by the wind and wave models and fetch limitations cause the wave model performance to deteriorate. Model performance is better in winter when the wave conditions are well defined. On the whole, the new forecast system provides reliable forecasts. Future improvements include data assimilation and higher-resolution wind forcing.